Revisión de diferentes partes vegetales del Banano (Musa AAA) como alternativa para la aplicación de productos biodegradables en el Ecuador - Carbo Pincay, Lisseth Tatiana (2024)
In Ecuador, there are different opinions about the viability of using plant by-products from bananas as raw materials to innovate new products, add value to existing products and, in particular, replace those that come from non-renewable sources. The stated objective is to identify products from plant parts of bananas, with the purpose of applying them in biodegradable products. This project has been developed by collecting all types of information from recent years through research and analysis of various scientific articles, books and magazines available in various sources. In this context, a review of the benefits, applications and uses of the rachis, pseudostem, and leaves will be carried out, thus determining which of them are the most usable, highlighting their potential application in pseudostem bioplastics due to their content of starch, cellulose, hemicellulose. and lignin, these natural components provide the bioplastic with several properties that make it suitable for a wide variety of applications such as disposable utensils, food packaging, shopping bags. On the other hand, paper mache pulp from banana leaves stands out for its fibrous, cellulosic and flexible content, which makes it suitable for obtaining it, its availability and resistance being a popular option in the creation of A variety of decorative objects The banana leaf contains a wide variety of components that can be used for various purposes in biodegradable products.